Fieldwork for Writing Urban Places: Working Group 4 - Santiago Baptista, Luis; Velevski, Slobodan (Writingplace, 2023)
Fieldwork within the COST Action Writing Urban Places aims to research the possibilities of interdisciplinary narrative practices in understanding and activating urban contexts in European cities. As a way to sustain and foster the meaningfulness, appropriation and integration of places and their communities, it intends to reflect and test its concepts and methodologies in reality. Fieldwork bridges the link between investigation and practice, knowledge and performativity, thinking and doing. Gathering expertise of diverse disciplines, from the social and human sciences to urbanism, architecture and art, fieldwork is debated in the context of the spatial practices, with their critical and aesthetic dimensions. By visiting places (Almada, Limerick, Tallinn, Osijek, Tampere, Çanakkale, Skopje, Tirana, Delft) and sharing knowledge, collecting existing narratives and implementing new ones, crossing local inhabitants and international participants, fieldwork activities allow for a deeper involvement in physical and social contexts and an active engagement with communities and stakeholders.